2016
DOI: 10.1111/hcre.12097
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Mode of Information Presentation: Effects on Younger and Older Adults' Attention and Recall of Online Information

Abstract: Previous studies have mainly focused on tailoring message content to match individual characteristics and preferences. This study investigates the effect of a website tailored to individual preferences for the mode of information presentation, compared to 4 nontailored websites on younger and older adults' attention and recall of information, employing a 5 (condition: tailored vs. text, text with illustrations, audiovisual, combination) × 2 (age:younger vs. older [≥65] adults) design (N = 559). The mode-tail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 47 publications
2
36
0
Order By: Relevance
“…If possible, display options on 1 page, for example, first provide an overview with options, and then (after visitors choose what information they wish to read) the relevant information.” Limited information on a webpage would make it possible to provide patients with a large font size to enable them to avoid scrolling. We agree with Gokani et al that more research is needed on other ways of tailoring that could benefit older patients, such as mode tailoring and message frame tailoring, next to content tailoring (see work by our research group [3,4]).…”
supporting
confidence: 75%
“…If possible, display options on 1 page, for example, first provide an overview with options, and then (after visitors choose what information they wish to read) the relevant information.” Limited information on a webpage would make it possible to provide patients with a large font size to enable them to avoid scrolling. We agree with Gokani et al that more research is needed on other ways of tailoring that could benefit older patients, such as mode tailoring and message frame tailoring, next to content tailoring (see work by our research group [3,4]).…”
supporting
confidence: 75%
“…Previous work by our group (Bol, ; Bol, Scholz et al., ) and others (Lustria et al., ; Smit, Linn, & van Weert, ) has indicated a need for tailored information provision via different modalities, particularly among older cancer patients. Therefore, an additional experimental study was conducted to investigate how online health information could be tailored to individual preferences and abilities regarding the modality of information presentation ( n ≈ 563; Nguyen, Smets, Bol, Loos, & Van Weert, ; Nguyen et al, ). “Mode tailoring”, by enabling users to self‐select whether they would like to receive the information via text, illustrations and/or videos, was effective in increasing attention to and recall of online health information, and satisfaction with the attractiveness of health websites in older adults.…”
Section: Resultsmentioning
confidence: 99%
“…“Mode tailoring”, by enabling users to self‐select whether they would like to receive the information via text, illustrations and/or videos, was effective in increasing attention to and recall of online health information, and satisfaction with the attractiveness of health websites in older adults. Based on these insights, we integrated a horizontal built‐in navigation bar, enabling viewers to self‐select whether they would like to receive the information via textual, visual and/or audiovisual information (Nguyen et al., , ; Soroka et al., ). Users could switch and change modalities at any time while viewing the information.…”
Section: Resultsmentioning
confidence: 99%
“…According to this more user-initiated approach, patients can choose themselves if and how they prefer adherence support. This approach is expected to exert persuasive effects [11,40]. Future research should further explore these new approaches.…”
Section: -1426mentioning
confidence: 99%
“…As rightfully pointed out by a recent study [12], very little work has been conducted on the underlying mechanisms of tailoring. The few studies exploring these underlying mechanism indeed found that the effects of tailored interventions are mediated by perceived relevance, attention and elaboration [12,40]. Future research is needed to examine the pathways of these processing variables to Linn, A.J., Dijk, L. van, Weert, J.C.M.…”
Section: -1426mentioning
confidence: 99%